The Anesthesia & Anesthetists of the First Open Heart Surgery of Bangladesh - Hosain, Suman Nazmul; Amin, Farzana; Ferdous, Shahnaz (Bangladesh Heart Journal, 2021)
Although a few closed heart operations were performed in the late 1960s, well organized approach to open heart surgery began in Bangladesh only after establishment of Institute of Cardiovascular Diseases (ICVD) in 1978. A Japanese team of surgeons, anesthetists, nurses and technicians provided extensive support in capacity building of the local human resources. Ultimately the first open heart surgery of Bangladesh, the direct closure of Atrial Septal Defect of an 18 year old college student, was performed on 18th September 1981. It was great news of that time. People came to know about the success story of the ICVD director then Colonel M Abdul Malik, a renowned cardiologist cum team leader and the Bangladeshi surgeon duo Dr M Nabi Alam Khan and Dr S R Khan. But somehow the anesthetists, an important part of the team were out of focus and have been forgotten over time. Led by Prof Khalilur Rahman, the anesthetist team of the day included Dr Nurul Islam, Dr Abdul Hadi, Dr Delowar Hossain, Dr A Y F Ellahi Chowdhury and Dr Monir Hossain. This article is an attempt to remind their contribution and expressing respect and gratitude to the anesthetists of that pioneering team. Bangladesh Heart Journal 2021; 36(1) : 55-60